LURKING, MAKING YOURSELF INVISIBLE AND SHRUGGING IT OFF – DIGITAL USERS’ COPING STRATEGIES IN DATAFIED EVERYDAY LIVES - Hartley, Jannie Møller (AoIR Selected Papers of Internet Research, 2020)
This paper investigates how audiences are coping with the digital platforms that they encounter in their everyday lives and how they feel about that these platforms are tracking, collecting data and mining data. By means of a bottom-up approach, we seek to direct scholarly attention at ordinary users’ self-reflexive (and increasingly) ambiguous perception and discursive articulation of their practices of algorithmic delegation. We aim to map the mundane data routines and habits of coping with data anxieties and thus ordinary users’ coping strategies (Pink, Lanzeni, & Horst, 2018). The analysis is empirically grounded in focus groups carried out in 2018 and 19 in Roskilde, Denmark, with a total of 34 participants of different ages and education background in order to increase homogeny and productivity in group discussions (Bloor, Frankland, Thomas, & Robson, 2012). The focus groups were transcribed and analysed in relation to Kennedy et. al.’s work on contextual integrity in practice (Kennedy et al., 2015), defined as case-by-case assessments of whether data mining practices can be considered to be reasonable. This enables us to show how different coping strategies are employed depending on the context of the habitual situation and digital routines (fx work vs. private life), the data collected (fx sensitive to non-sensitive data), and the platform the audiences engages with (fx private vs. public, national vs. international platforms and apps. The paper identifies four overall coping strategies, coping by absence, coping by trust, coping by minimizing risk and coping by apathy.